Microstructural and Mechanical Analysis of Sintered Powdered Aluminium Composites - Rajesh Kumar Behera; B. P. Samal; S. C. Panigrahi; K. K. Muduli (Advances in Materials Science and Engineering)
The present material world needs strong research studies for producing varieties of composite materials which have light weight and high strength with better performances. This leads to the introduction of materials through powder metallurgy technique. The main objective is to discover an aluminium matrix composite having enhanced characteristic performances and properties beyond the currently available materials. The current study has been carried out to develop an attractive composite having high strength, light weight, easy machinability, appreciable density, and low manufacturing cost. Aluminium powders of 99.55% purity and 325 mesh sizes are mixed with alloying metals such as copper, magnesium, silicon, and silicon carbide powders in a precisely controlled quantity. The result was found with better mechanical properties, and the XRD patterns were studied in the matrix at different intensities, showing the interfacial bonding of elements gives rise to increase in strength.